Hadith Perspective By Islamic Counselor As Media Da'wah At The Religious Affair Ministry - Dzurrotun Afifah Fauziah (IAIN Salatiga, 2021)
This research examines more deeply about the exploration of the dedication of Islamic extension agents in remote areas of the archipelago. Extension officers as the front line for The Religious Affairs Ministry who are in direct contact with community. Extension workers become inspirational who contribute significantly to the mental development of the community. The teachings of peace and happiness to be spiritual for society are well emphasized through social communication. This study uses library data collection techniques (library research), namely by using librarian sources in the process of obtaiing answers to problems in the study. The sources used by the authorare books and journals that discuss topics related to the author’s discussion topic. The research results obtained by the authors include; Islamic extension workers across the archipelago have different challenges according to the situation and conditions of the assignment given, there are still many extension workers in remote cities with inadequate mobility, with the growing era in this technological era extension officers are required to have a ore initiative based da’wah communication stategy. To better attract the public.